Hormone concentrations throughout uncomplicated pregnancies: a longitudinal study. Issue 1 (December 2016) - Schock, Helena; Zeleniuch-Jacquotte, Anne; Lundin, Eva; Grankvist, Kjell; Lakso, Hans-Åke; Idahl, Annika; Lehtinen, Matti; Surcel, Heljä-Marja; Fortner, Renée
Abstract Background Evidence suggests that the hormonal milieu of pregnancy is an important determinant of subsequent cancer and other chronic diseases in both the mother and the offspring. Many of the existing maternity and birth cohorts include specimens drawn only once during pregnancy. How well a single blood specimen collected during a pregnancy characterizes exposure to these hormones throughout gestation, and also in subsequent pregnancies, is not well understood. Methods We used serial serum samples from 71 pregnant women (25 primiparous, 25 multiparous, and 21 with two consecutive pregnancies) with natural, complication-free pregnancies and a healthy offspring at term who participated in a population-based screening trial for congenital infections in Finland between January 1st, 1988 and June 30, 1989 and provided a blood sample in each trimester. Results Hormone levels were more strongly correlated between consecutive trimesters of a pregnancy than between the 1st and 3rd trimester (e.g., estradiol, rT1 vs. T2  = 0.51 and rT2 vs. T3  = 0.60, p  < 0.01; rT1 vs. T3  = 0.32, p  < 0.05). Concentrations of sRANKL remained stable throughout gestation, whereas estradiol, estrone, progesterone, testosterone, prolactin, and osteoprotegerin increased throughout pregnancy. First trimester hormone concentrations explained less of the variation in the third trimester on their own than second trimester hormone levels (e.g. estradiol R2 T1  =  16 % and R2 T2  = 42 %). Addition of maternal (e.g., smoking) and/or child characteristics (e.g., sex) improved the accuracy of the 3rd trimester estimates for some of the hormones. Conclusions One hormone measurement in early pregnancy, in conjunction with maternal and fetal characteristics, permits estimation of 3rd trimester hormone concentrations. Therefore, single hormone measurements available from maternity cohorts are suitable to quantify hormone exposure during pregnancy. To our knowledge, we provide the first data on correlations between hormone concentrations both across trimesters of a single pregnancy, as well as between two subsequent pregnancies.